Predictors of poor cognitive status among older Malaysian adults: baseline findings from the LRGS TUA cohort study - Vanoh, Divya; Shahar, Suzana; Che Din, Normah; Omar, Azahadi; Chin, Ai Vyrn; Razali, Rosdinom; Ibrahim, Rahimah; Tengku Abdul Hamid, Tengku Aizan (Springer, 2016)
Background: Concepts of successful aging (SA), usual aging (UA), and mild cognitive impairment (MCI) have been developed to identify older adults at high risk of Alzheimer's diseases (AD), however, the predictors have rarely been investigated in a single study. Thus, this study aims to explore the risk factors of MCI as compared to UA and SA among older adults, in a large community based cohort study in Malaysia. Method: 1993 subjects from four states in Malaysia were recruited. A comprehensive interview-based questionnaire was administered to determine socio-demographic information, followed by assessments to evaluate cognitive function, functional status, dietary intake, lifestyle and psychosocial status. Risk factors of cognitive impairment were assessed using the ordinal logistic regression (OLR). Result: The prevalence of SA, UA and MCI in this study was 11, 73 and 16 % respectively. OLR indicated that higher fasting blood sugar, hyperlipidemia, disability, lower education level, not regularly involved in technical based activities, limited use of modern technologies, lower intake of fruits and fresh fruit juices and not practicing calorie restriction were among the risk factors of poor cognitive performance in this study. Conclusion: This study will be a stepping stone for future researchers to develop intervention strategies to prevent cognitive decline.